Me and Ms. Too - Ruby, Laura (Balzer + Bray, an imprint of HarperCollinsPublishers, 2022)
For as long as Molly can remember, it's always just been her and Dad. Dad, who likes to splash in the pool, who likes to spin at the park, who bakes the best cookies around. But that was before Dad married Ms. Too. Ms. Too doesn't like to splash. She doesn't like to spin. And she can't bake anything. "But Molly, you used to love Ms. Too." That was before, when she was Molly's favorite librarian. Now everything has changed. But as Molly and Ms. Too are about to discover, maybe change isn't always scary. Maybe change can be the best thing of all.--